The head of the Doryphoros from the “Palestra” of Hadrian’s Villa in Tivoli (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2025)
The head of the Doryphoros, discovered during a brief survey in the so-called ‘Palestra’ of Villa Adriana, is framed among the attestations of works by Polykleitos in the Tiburtine residence. Analysis of the work reveals a dual purpose, both gymnastic/athletic, confirming Pirro Ligorio’s original identification of a gymnasium, and cultic, given the presence of statues of Egyptian deities. The choice of the Doryphoros type, and more generally of Polykleitos types present in the Villa, shows the special link between the imperial patronage and the Argive sculptor.
Keywords: Pirro Ligorio; Cardinal Marefoschi; Conte Fede; Teatro Greco; copies of the statues